Context Awareness Technology Using Parallel Mining for Ambient Assisted Living System - Vivek, J; Maharnisha, Gandla; Roopesh Kumar, Gandla; Karun Sagar, Ch; Arunraj, R (International Journal of Engineering and Technology, 2018)
InÂ thisÂ paper,Â contextÂ awarenessÂ isÂ aÂ promisingÂ technologyÂ thatÂ providesÂ health care services and a nicheÂ area of big data paradigm. TheÂ Â driftÂ inÂ Knowledge Â DiscoveryÂ fromÂ DataÂ refersÂ toÂ aÂ setÂ ofÂ activitiesÂ designedÂ to refine andÂ extractÂ new knowledge from complexÂ datasets.Â TheÂ Â proposedÂ modelÂ facilitatesÂ aÂ parallelÂ miningÂ ofÂ frequent item sets for Ambient Assisted Living (AAL) System [a.k.a. HealthÂ Care [System]Â ofÂ bigÂ data thatÂ resideÂ Â insideÂ aÂ cloudÂ environment.Â WeÂ extendÂ aÂ knowledgeÂ discovery framework for Â processingÂ andÂ classifyingÂ theÂ abnormalÂ conditions of patients having fluctuations in Blood Pressure (BP) and Heart Rate(HR) and storingÂ this dataÂ setsÂ calledÂ Big dataÂ into Cloud to access fromÂ anywhereÂ Â whenÂ needed.Â Â ThisÂ Â accessed data is used to compare the new data with it, which helps to know the patients health condition.Â Â